After the Dust Has Settled: Enduring Teacher Unionism - Bascia, Nina; Maharaj, Sachin (Critical Education, 2022)
The question this article attempts to answer is, how can teacher unions take advantage of the opportunities afforded by their organizational structures while minimizing the factors that have stood in the way of educational and societal change? Drawing from examples of teacher unions’ strategies from studies of several organizations outside of the United States, it provides examples of how teacher unions have “crafted coherence” between their inner dimensions and outward-looking strategies, and contributes to the advancement of critical education by recommending ways that teacher organizations can more effectively support social justice and social change.